2016
DOI: 10.1590/1806-9061-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lycopene Addition on the Chemical Composition, Sensory Attributes and Physicochemical Properties of Steamed and Grilled Turkey Breast

Abstract: The aim of this study was to determine the effect of lycopene addition to the curing mixture for steamed and grilled breast muscles on the chemical composition, sensory attributes and physicochemical parameters of the final products. The experimental material comprised a total of 48 breast muscles of Hybrid XL turkeys aged 15 weeks and fed commercial pelleted diets. The material was divided into three groups (control, experimental groups I and II). Sixteen breast muscles (8 left and 8 right) were assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The colour evaluation of meat samples showed that the concentration of TP had significant (P < 0.05) effects on the colour of raw chicken sausage samples (Table 2). Similar results have been observed in previous studies by adding tomato products to the color changes of grilled turkey breast (Skiepko et al, 2016), minced chicken (Alves et al, 2012), beef (Østerlie & Lerfall, 2005) and pork (An et al, 2019) samples.…”
Section: Color Measurementssupporting
confidence: 91%
“…The colour evaluation of meat samples showed that the concentration of TP had significant (P < 0.05) effects on the colour of raw chicken sausage samples (Table 2). Similar results have been observed in previous studies by adding tomato products to the color changes of grilled turkey breast (Skiepko et al, 2016), minced chicken (Alves et al, 2012), beef (Østerlie & Lerfall, 2005) and pork (An et al, 2019) samples.…”
Section: Color Measurementssupporting
confidence: 91%
“…Color is one of the most important meat quality measures for consumers and can be changed and corrected with the use of additives and colorings (Skiepko et al, 2016). Table (6) illustrated that the mean score of flavor was higher in sample treated with taro mucilage T1 (9.00) than control sample (8.90).From the same Table mean flavor scores followed a declining trend after four and six months compared to zero time and after two months.…”
Section: Sensory Evaluation Of Canned Meat Supplements With Differentmentioning
confidence: 89%